Reconfigurable magnonic mode-hybridisation and spectral control in a bicomponent artificial spin ice - Jack C. Gartside (Nature Portfolio, 2021)
Reconfigurable magnonic crystals (RMC), comprising nano-patterned arrays of magnetic elements, can host a wide variety of spectrally-distinct microstates with great potential for functional magnonics. Here, Gartside et al, present an RMC with four distinct microstates, possessing diverse magnonic properties and exhibiting reconfigurable magnon mode hybridisation.